Correlation among 16 biological factors [p53, p21(waf1), MIB-1 (Ki-67), p16(INK4A), cyclin D1, E-cadherin, Bcl-2, TNF-α, NF-κB, TGF-β, MMP-7, COX-2, EGFR, HER2/neu, ER, and HIF-1α] and clinical outcomes following curative chemoradiation therapy in 10 patients with esophageal squamous cell carcinoma - SHIBATA-KOBAYASHI, SHINO (D.A. Spandidos, 2013)
The expression levels of 16 proteins were analyzed to identify prognostic correlations in esophageal squamous cell carcinoma (ESCC) treated with concurrent chemoradiation therapy (CCRT). The immunohistochemical expression levels of p53, p21(waf1), molecular immunology borstel-1 (MIB-1, Ki-67), p16(INK4A), cyclin D1, E-cadherin, Bcl-2, tumor necrosis factor (TNF)-α, nuclear factor (NF)-κB, transforming growth factor (TGF)-β, matrix metalloproteinase (MMP)-7, cyclooxygenase (COX)-2, epidermal growth factor receptor (EGFR), human EGFR type 2 (HER2/neu), estrogen receptor (ER) and hypoxia-inducible factor (HIF)-1α were studied in 10 cases of ESCC treated with CCRT. The patients underwent CCRT between 2000 and 2010. The mean patient age was 68.1 years (range, 46-80 years). The numbers of patients in stages I, II, III and IV of the disease were 2, 2, 3 and 3, respectively. Of the tumors, 8 were positive for p53, 6 for p21(waf1, 7) for MIB-1 (Ki-67), 7 for p16(INK4A), 7 for cyclin D1, 8 for E-cadherin, 3 for Bcl-2, 0 for TNF-α, 5 for NF-κB, 7 for TGF-β, 9 for MMP-7, 7 for COX-2, 5 for EGFR, 1 for HER2/neu, 1 for ER and 7 for HIF-1α. The 2-year overall survival rate of patients expressing high levels of MIB-1 was 71% (±17%) compared with 0% (P=0.019) for those expressing low levels. For NF-κB, the rate was 0% for patients with high levels compared with 100% (P<0.018) for those with low levels. The 2-year local control rates of HER2/neu were 0% in patients expressing high levels and 88% (±12%) in patients expressing low levels (P=0.027). The 2-year disease-free survival rates of HER2/neu and ER were 0% for patients expressing high levels compared with 56% (±17%) for those with low levels (P=0.027). There were no significant correlations between the expression levels of the other proteins and clinical outcomes. In the present study, high levels of MIB-1 and low levels of NF-κB, HER2 and ER were shown to be good prognostic factors following definitive CCRT for ESCC.